Diálogos e contribuições da cultura da paz, na prevenção do ato infracional e da violência - Pereira Junior, Luciano Aparecido (2020)
The study aimed to understand how the Culture of Peace, as an essential aspect of Health Promotion, can assist in the prevention of the offense and violence. The theoretical framework initially proposes a reflection on the historical process of adolescence, based on the understanding that the individual is a developing subject. Discusses the correlations between social determinants, adolescence within full protection, provided for in the Statute of Children and Adolescents (ECA), in addition to a brief history on Health Promotion and associations with the concept of Culture of Peace, in the perspective of prevention of violence. There are correlations between Health Promotion and the Sustainable Development Goals (SDGs), especially SDG 16, which establishes peace, justice and effective institutions. In this research, an integrative review was initially carried out on the Scielo, Pepsic, Redalyc, Google Scholar platforms and on Brazilian government documents and international documents, using the following health descriptors: adolescents, socio-educational measures, health promotion and culture of peace . The field research was carried out in a city in the interior of São Paulo, within the scope of the Specialized Center for Social Assistance (CREAS), along with socio-educational measures in an open environment, through five stages. Firstly, adolescents were invited to comply with an Assisted Freedom socio-educational measure, among them, twelve adolescents participated, according to the inclusion and exclusion and availability criteria. Subsequently, a workshop was held, addressing the theme of Health Promotion and Culture of peace with adolescents. Then, six focus groups were held with the teenagers, with trigger themes and semi-structured interviews, with parents and guardians. And finally, there was the documentary analysis of the Individual Service Plan (PIA), which is an instrument developed with the reference technician, along with the adolescent and the family. The data were analyzed through content analysis and Social Constructionism, as a theoretical-methodological framework. The adolescents 'and parents' speeches are permeated by family conflicts, inequities, experienced violence, cultural aspects, non-access to public services, prejudices and difficulties in accessing the labor market. Problems were found in the support network in the territories, problems in the management of socio-educational measures, with reduced teams, to assist the adolescent and his family, not only in breaking the offense, but mainly in guaranteeing social rights. All the knowledge built during the workshop and the focus groups enabled reflections on the Culture of Peace, since the offense is the result of several factors: limitations of public management, territory, services, the cycle of misery and poverty and of families and bonds. Understanding the territories is essential to dialogue and build more effective strategies and actions that prioritize a better quality of life and well-being for adolescents and their families. In the reality studied, the effective and participatory Culture of Peace is still a challenge to be conquered. Keywords: Adolescence. Culture of Peace. Socio-educational Measures. Health Promotion. Violence.